Digitalising the Shared Experience: Interconnected Dramaturgy and the Role of Media in the Tri-National Performance Phone Home. Issue 3 (4th May 2018) - Beck, Sarah
ABSTRACT: Phone Home was a collaborative performance project between three theatre companies (Upstart Theatre, Pathos München and Highway Productions), across three countries (Britain, Germany and Greece), with performances taking place simultaneously in venues in three cities (London, Munich and Athens) from 21–30 October 2016. The telematic performance examined themes of home and technology in the wake of the ongoing refugee crisis and migration across Europe. Phone Home 's broadcasted and connected scenes were made possible by video-conferencing, connecting the audiences both of the simultaneous performances across three cities and its live-streamed broadcast. This article investigates the use of technology in the research and devising process of this tri-national collaboration while examining the critical role media plays in live performance. In order to explore the implications of telematics in collaborative theatre-making, the author interviewed the collaboration's practitioners, examining the use of technology through the research and development process. The author argues that it becomes necessary to critically reflect on how creative teams negotiate technology and content—particularly when stories are inspired by real people's experiences of displacement—in the dramaturgical process in an effort to understand the effectiveness of telepresence in transnational collaborations, as well as the problems telepresence presents.